A common stage : theater and public life in medieval Arras - Symes, Carol (Conjunctions of religion & power in the medieval past., 2007)
"Medieval Arras was a thriving town on the frontier between the kingdom of France and the county of Flanders, and home to Europe's earliest surviving vernacular plays. In A Common Stage, Carol Symes undertakes a cultural archaeology of these artifacts, analyzing the process by which a handful of entertainments were conceived, transmitted, received, and recorded during the thirteenth century. She then places the resulting scripts alongside other documented performances: the crying of news, publication of law, preaching of sermons, and arrangement of civic spectacles. A Common Stage thus challenges the prevalent understanding of theater history while offering the first comprehensive history of a community often credited with the invention of French as a powerful literary language."--Jacket